Analysis of telecom operators’ IoT strategy from the perspective of 2G/3G transition - Xiaozhong LIU; Junyu FANG; Yongbin JIANG (Dianxin kexue)
In the context of 2G/3G transition, it is a general trend for NB-IoT and LTE Cat.1 to undertake their business development.On the basis of reviewing and analyzing the current status and trends of the 2G/3G-IoT (Internet of things) business, sorting out the IoT business development strategies of the three major domestic telecom operators at the terminal, network and application levels, the three existing business models of telecom operators in the NB-IoT and LTE Cat.1 business area were summarized, including traffic-oriented, platform-supported, and application-enabled.Finally, from three aspects of business opportunity expansion, product marketing and team services, the future upgrade of the business model was prospeted.